Wittenwiler's "Ring" and the Anonymous Scots Poem "Colkelbie Sow" Two Comic-Didactic Works from the Fifteenth Century - Fenwick Jones, George (UNC Studies in the Germanic Languages and Literatures, 1956)
Heinrich Wittenwiler's "Ring", written in a Swiss dialect and presented in English translation for the first time in this 1956 volume, is a comic-didactic and religious allegory that documents late medieval views on many aspects of literature, history, law and religion. Besides his translation of "Ring", Jones adds an exposition on the text as well as a translation of the Middle Scots poem "Colkelbie Sow" with a comparative analysis of the two works.